Evolution of the methyl directed mismatch repair system in Escherichia coli - Putnam, Christopher D. (DNA Repair (Amst), 2015)
DNA mismatch repair (MMR) repairs mispaired bases in DNA generated by replication errors. MutS or MutS homologs recognize mispairs and coordinate with MutL or MutL homologs to direct excision of the newly synthesized DNA strand. In most organisms, the signal that discriminates between the newly synthesized and template DNA strands has not been definitively identified. In contrast, Escherichia coli and some related gammaproteobacteria use a highly elaborated methyl-directed MMR system that recognizes Dam methyltransferase modification sites that are transiently unmethylated on the newly synthesized strand after DNA replication. Evolution of methyl-directed MMR is characterized by the acquisition of Dam and the MutH nuclease and by the loss of the MutL endonuclease activity. Methyl-directed MMR is present in a subset of Gammaproteobacteria belonging to the orders Enterobacteriales, Pasteurellales, Vibrionales, Aeromonadales, and a subset of the Alteromonadales (the EPVAA group) as well as in gammaproteobacteria that have obtained these genes by horizontal gene transfer, including the medically relevant bacteria Fluoribacter, Legionella, and Tatlockia and the marine bacteria Methylophaga and Nitrosococcus.